The effects of Maslow's hierarchy of needs on zakah distribution efficiency in Asnaf assistance business program / Maheran Zakaria, Junaidah Hanim Ahmad and Nur Ain Abdul Malek - Zakaria, Maheran; Ahmad, Junaidah Hanim; Abdul Malek, Nur Ain (Faculty of Accountancy & Accounting Research Institute (ARI), 2014)
The objective of this study is to examine the effects of Maslow s hierarchy of needs on zakah distribution efficiency. Mas low's hierarchy of needs posits that humans strive to achieve five levels of needs in hierarchical order, starting from physiological needs and followed by the needs for safety, social, self-esteem and self actualization. Zakah distribution efficiency is then evaluated using Balanced Score Card with four dimensions, namely customer satisfaction, internal process, knowledge worker and financial management. Three hundred recipients of the Asnaf Assistance Business Program conducted by Majlis Agama Islam Kelantan (MAIK, Islamic Religious Council ofKelantan) completed a questionnaire prepared for the purpose of the study. Data was analysed using Statistical Package for Social Sciences (SPSS) and Analysis of Moment Structure (AMOS). It can be concluded from the findings that Mas low s hierarchy of needs has positive effects on zakah distribution efficiency. This proves that the distribution of zakah in sustainable forms could satisfy recipients' needs and help them maintain a decent quality of life.